Histologia do testículo aposto a um retalho intestinal (cecal) em ratos - Rodrigues Júnior, Saulo (2008)
The aim of this experiment is to study, histologically, the testicular vascularization, after apposition of an intestinal pedicle flap to the testicle of Wistar rats, as well as the consequences of procedure for the gonads. It was used 53 Wistar male rats with age varying between 12 and 16 months, and weighing between 290g and 440g were selected into a laboratory rats population, apparently healthy and divided into 4 groups, GI, GII, GIII and GIV. The rats, with a 12h fast for solid food were submitted to anesthesia using Cetamine hydrochloride (40 mg /Kg) and a 2% Xylazine hydrochloride solution (1mL /Kg). The animals were weighed 30 minutes before procedures and 30 minutes before euthanasia. The surgical procedures were randomly made in rats of GI, GII and GIII, but the rats of GIV were only reserved, in the same conditions, as a control group. After procedures, the animals were treated with the same food, offered after anesthetic recovery, ad libitum and placed in an environmental with the same characteristics. Seven rats were excluded. GI: submitted to celiotomy, mobilization, by traction, of the right testicle (RT) to the abdomen, cecal flap suture to the RT and cavity closure. GII: celiotomy, mobilization of the RT to the abdomen, fixation of RT into abdomen (peritoneum) and cavity closure. GIII: celiotomy, mobilization of the RT to the abdomen, RT exposition to air (3 minutes), reposition into scrotum and cavity closure. GIV: not operated on (control group). Euthanasia was done 20 days after and the testicles were submitted to histological analysis. A Morfometric analysis (histometry) was done and lesions score classification was applied. Testicular vascularization was studied with comparison between GI and GIII. The weight s averages were compared among the groups. A p < .05 was considered. The GI RT diameters were not different to GII RT and all have decreased size in comparison with RT of GIII and GIV. The lesions score s average was 5.83 in the RT of GI and 3.3 in GII, without statistical difference. The vascularization s average in the RT of GI was 16.9 vessels in 400X augmentation field. In the GIII the average was 0.96 to the RT and 0.92 to left testicles. The weight s average in GI was similar with GII but different of GIII and GIV. There was significant vascularization in the testicles with intestinal flaps. Testicle lesions were observed, but the intestinal flap wasn t a proved cause. The anesthesia, the surgical trauma response the manipulation of the testicles and the weigh variations didn t cause lesions or diameters decrease in the testicles.